2020
DOI: 10.2458/v27i1.23757
|View full text |Cite
|
Sign up to set email alerts
|

The strategy of shifting cultivators in West Kalimantan in adapting to the market economy: empirical evidence behind gaps in interdisciplinary communication

Abstract: Issues of climate change and expansion of large-scale land acquisition for industrial plantations continue to ravage the shifting cultivation system that 300–500 million subsistence farmer households depend on. In Indonesia, particularly in Kalimantan and Sumatera, village communities continue to practice shifting cultivation amidst the conversion of lands into industrial plantations. The rampant conversion of farmer's land by large scale companies based in the market economy has resulted in the decline of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The qualitative achievement such as changing attitudes, accepting differences of opinion, and readiness to collaborate with other parties (between communities, government, and NGOs) in the conflict transformation phase since the early reform era opened up an entry point into the technical implementation phase. Integrative policy support and directed technical activities were responded through the collaboration between the NGOs and forestry apparatus in the field for transformation of role, technical capacity building for the community in terms of agro-product processing, reinforcement of social institutions, and market network for the community or farmers (Maring, 2020). It is observed that collaboration and conflict transformation approaches are important processes that lay the foundation for social forestry movement in the field (Markopoulos, 2012).…”
Section: Significance Of Conflict Transformation Approach and Multi-stakeholder Collaborationmentioning
confidence: 99%
See 1 more Smart Citation
“…The qualitative achievement such as changing attitudes, accepting differences of opinion, and readiness to collaborate with other parties (between communities, government, and NGOs) in the conflict transformation phase since the early reform era opened up an entry point into the technical implementation phase. Integrative policy support and directed technical activities were responded through the collaboration between the NGOs and forestry apparatus in the field for transformation of role, technical capacity building for the community in terms of agro-product processing, reinforcement of social institutions, and market network for the community or farmers (Maring, 2020). It is observed that collaboration and conflict transformation approaches are important processes that lay the foundation for social forestry movement in the field (Markopoulos, 2012).…”
Section: Significance Of Conflict Transformation Approach and Multi-stakeholder Collaborationmentioning
confidence: 99%
“…In order to achieve such goals, the community needs to be supported through technical capabilities to manage the forest. Enhancing the community's capacity was, thus, a crucial aspect in developing social forestry (Boedhihartono, 2017;Maring, 2020;Nuddin et al, 2019;Pujo et al, 2018;Santika et al, 2017). Achieving the target area of social forestry had to take into consideration the process of fair land distribution as there were many administrative weaknesses and economic interests maintained by local actors (Nurlia et al, 2020;Royer et al, 2018).…”
Section: Policies That Integrate and Mobilize Technical Activities Of Social Forestrymentioning
confidence: 99%
“…In a broader context, sociocultural changes in rural society are constantly associated with change in a broader social space. External socioeconomic intervention may penetrate villages and transit new values into village communities (Bettencourt et al, 2015;Maring, 2020;Uslu et al, 2020). Interventions from outside of the village, such as spatial change policy, resource vulnerability, and economic and social inequality, may mobilize villagers into the labor force in rural areas through an urbanization process and cause poverty in rural areas (Lan, 2021;Rudiarto et al, 2018).…”
Section: Introductionmentioning
confidence: 99%